Management of the results budget and its influence on the quality of public expenditure in the municipality district Chaglla - Pachitea - Huanca-Isidro, Marilu D. (2019)
The objective of the present investigation was to demonstrate how the management of the budget by results in the quality of the expenses in the District Municipality of Chaglla - Pachitea influences, where different workshops were developed whose objective was to train them technically and to develop their abilities on budget management. The research method used is the Scientific Method, the level of research is quasi experimental, the research design used in the present investigation was quasi experimental, where it allowed us to relate with two or more data of a set of subjects with the intention of Demonstrate the influence, which is our case. The sample of the present investigation work is represented by a total of 26 workers of the Municipality of Chaglla. The results obtained in the present investigation show that the majority of workers stated that quality spending means knowing how to use public resources in goods and services that favor the standard of living of the population. It was concluded that the implementation of the Results Budget in Peru's local governments improves the quality of public spending since they are intended to promote the living standards of the population.